2016
DOI: 10.4236/fns.2016.71005
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Cadmium in Tissues of Cacao Trees and Soils in Plantations of Trinidad and Tobago

Abstract: The primary source of cadmium in cocoa beans has been linked to its direct uptake by the cacao plant from cadmium contaminated soils. This research was conducted to evaluate and interpret significant relationships between cadmium levels in tissues of the cacao plant and soils from cocoa-growing areas in Trinidad and Tobago. Total (HNO3-extractable) concentrations of cadmium in both tissues and soils were determined. The levels of cadmium measured varied in the order: leaves > pods > shells > nibs > soil. Cadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
1
21
1
Order By: Relevance
“…Considering the average weight fractions for nib (0.93) and testa (0.07), 91% of the total bean Cd was located in the nib and 9% in the testa in unfermented cacao beans. In accordance to the present work, Ramtahal et al (2016) reported significantly higher Cd concentrations in testa (0.44-4.41 mg Cd kg -1 ) compared to nibs (0.35-3.82 mg Cd kg -1 ) for unfermented cacao beans from Trinidad and Tobago. Lewis et al (2018) reported more than two-fold higher Cd concentrations in the testa (average 1.83 mg kg -1 ) compared to those in the nibs (average 0.88 mg kg -1 ) for unfermented cacao beans from the same genetic group and grown in a common garden.…”
Section: Distribution Of CD In Unfermented Cacao Beanssupporting
confidence: 92%
See 3 more Smart Citations
“…Considering the average weight fractions for nib (0.93) and testa (0.07), 91% of the total bean Cd was located in the nib and 9% in the testa in unfermented cacao beans. In accordance to the present work, Ramtahal et al (2016) reported significantly higher Cd concentrations in testa (0.44-4.41 mg Cd kg -1 ) compared to nibs (0.35-3.82 mg Cd kg -1 ) for unfermented cacao beans from Trinidad and Tobago. Lewis et al (2018) reported more than two-fold higher Cd concentrations in the testa (average 1.83 mg kg -1 ) compared to those in the nibs (average 0.88 mg kg -1 ) for unfermented cacao beans from the same genetic group and grown in a common garden.…”
Section: Distribution Of CD In Unfermented Cacao Beanssupporting
confidence: 92%
“…Gramlich et al (2018) measured the Cd concentration in cacao from 55 farms in Honduras and did not find a significant difference between the Cd concentration in the pod husks (1.1 ± 0.2 mg kg -1 ) and that in the nibs (1.1 ± 0.1 mg kg -1 ). Conversely, Ramtahal et al (2016) reported higher Cd concentrations in the pod husks (0.53-4.49 mg Cd kg -1 ) compared to the nibs (0.35-3.82 mg Cd kg -1 ) for cacao from 45 farms in Trinidad and Tobago.…”
Section: Distribution Of CD In Unfermented Cacao Beansmentioning
confidence: 82%
See 2 more Smart Citations
“…Such work has shown that there are large regional variations of Cd levels in cacao beans, whereby problematically high concentrations are particularly prominent in Latin America and some Asian countries. [4][5][6][7][8][9][10][11][12][13] In these regions, the Cd concentrations of beans commonly exceed 0.6 to 0.8 mg kg À1 , 14 which is the approximate upper range for manufacturing cocoa products that are in accord with the new EU regulations. 8,15 For example, a recent study of more than 500 farms in Ecuador revealed that nearly 50% of the cacao beans had Cd concentrations that exceeded 0.6 mg kg À1 .…”
Section: Introductionmentioning
confidence: 99%